EKSPRESI SUFISTIK PEMANFAATAN BENTUK DALAM PUISI KUNTOWIJOYO - sujarwoko, sujarwoko; Sardjono, Sardjono (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2018)
The basic concept of poetry expression departs from the general statement that the poet is the creator. Sufistic expression is an expression of the poet's personal perception of his sufistic outlook. Therefore, sufistic expressions can be used as a tool to identify the characteristics of the poet. Kuntowijoyo, also has its own characteristics in the method of conveying the spiritual ideas of sufistic ideas. This study uses a qualitative design with researchers as the main instrument. The data of this study are poetry, stanzas, lines, and poetry diction related to the focus of the study. The research produced: 1) sufistic expression in the use of allegory forms, 2) sufistic expression in the use of philosophical forms; and 3) sufistic expression in the use of the form of Al-Barzanji. The three methods of conveying the poem as a means to express the rankings of spiritual beauty.